A novel real-time feedback pitch angle control system for vertical-axis wind turbines. Issue 195 (December 2019) - Chen, Linjun; Yang, Yuzhuo; Gao, Ye; Gao, Zheming; Guo, Yonghui; Sun, Lanxin
Abstract : Modern horizontal-axis wind turbines improve their performance by controlling the blade pitch, which is a well-developed technique in practical use. However, the application of this method in vertical-axis wind turbines (VAWTs) is restricted, due to continuous changes in both the relative wind velocity and angle of attack of the blade. In the study, through an in-depth aerodynamic analysis between the blade pitch and performance of VAWTs, a real-time feedback blade pitch control system is developed, which is based on the real-time flow velocity around the blade. Subsequently, a computational fluid dynamics method with FLUENT is constructed to evaluate the performance of the pitch control system on improving VAWT performance. The calculation method is verified via wind tunnel experimental data. Results indicate that real-time feedback control of the pitch angle increases the average power coefficient in a wide range of tip speed ratios (TSRs). At low TSRs, it significantly improves the starting performance by decreasing the occurrence of vortex shedding and flow separation on the blade surface. At high TSRs, it effectively increases the power coefficient of VAWTs. Additionally, at high TSRs, the power coefficient generally exceeds 0.3 and the maximal power coefficients of the VAWTs corresponds to 0.441. At high TSRs, when compared to the zero pitch, the power coefficient relatively increases by at least 12.7%. Highlights: A novel real-time blade pitch control system for VAWTs is developed. A method evaluates performance of pitch control system in CFD is developed. This pitch control system effectively improves power coefficient of VAWTs.